Verificação da eficiência e da eficácia do conjunto de métodos preventivos à contaminação em postos de combustíveis na cidade de São Paulo: uma contribuição à gestão de cidades - Alves, Adjane Brito (2019)
Sustainability needs to be inserted in the space of urban analysis, in different segments and economic activities, mainly in potentially polluting activities, as is the case of gas stations which is an important activity in the urban context. The objective of this study was to verify the efficiency and effectiveness of the set of contamination preventive methods, based on guidelines of relevant laws to the São Paulo State. Cases of recurrent contamination have been identified in establishments that have undergone restoration or new installations in the urban space. These cases were registered in the Register of Contaminated and Rehabilitated Areas of the Environmental Company of São Paulo State - CETESB. The processes of 49 gas stations registered with CETESB - Pinheiros were analyzed. Data were also collected from environmental legislation, technical standards, resolutions, manuals and scientific articles. Moreover, information was obtained, through a structured interview, with a specialist in contaminated areas of an environmental consultancy. After analysis, it was found that half of the gas station presented contamination contributions or cases of recurring contamination due to diverse situations, such as human error, failure in engineering procedures, mechanical failures, operational and procedural failures and even failures in procedures. intervention. The present study indicated that São Paulo State, despite having a national reference agency to management of contaminated areas, still lacks the necessary effectiveness and efficiency. The situation is the most critical for most Brazilian states, which do not have the same regulations and infrastructure for identifying and implementing prevention and mitigation procedures. The occurrence of contamination, in addition to harming the environment, the community and its surroundings, also harms the company's economy, since they need to bear the high costs of interventions that usually are between R$ 50,000.00 and R$ 2 million, depending on the complexity of the spill. The contamination sites also cause devaluation of real estate in the area, resulting a challenge for the management of cities that must be overcome with the implementation of new public policies that enable the inspection of all engineering procedures in the construction phase.